2021
DOI: 10.3390/pr9091537
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Cooling Crystallization in a Coiled Flow Inverter Crystallizer Technology—Design, Characterization, and Hurdles

Abstract: Continuous small-scale production is currently of utmost interest for fine chemicals and pharmaceuticals. For this purpose, equipment and process concepts in consideration of the hurdles for solids handling are required to transfer conventional batch processing to continuous operation. Based on empirical equations, pressure loss constraints, and an expandable modular system, a coiled flow inverter (CFI) crystallizer with an inner diameter of 1.6 mm was designed. It was characterized concerning its residence ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 90 publications
(259 reference statements)
0
12
0
Order By: Relevance
“…However, a stretching of the curve to the right can be seen as some found crystal diameters are above 125 mm. This stretching can also be seen in the evaluation of Schmalenberg et al The evaluation with CNN shows good results in the middle and especially in the high size ranges, which are clearly below the results of Schmalenberg et al [12,13,20] On the other hand, the evaluation with CNN in the low value ranges of the PSD is far from the results of the sedimentation analysis. This can be explained by the effects of watershed and roundness described above.…”
Section: Resultsmentioning
confidence: 78%
“…However, a stretching of the curve to the right can be seen as some found crystal diameters are above 125 mm. This stretching can also be seen in the evaluation of Schmalenberg et al The evaluation with CNN shows good results in the middle and especially in the high size ranges, which are clearly below the results of Schmalenberg et al [12,13,20] On the other hand, the evaluation with CNN in the low value ranges of the PSD is far from the results of the sedimentation analysis. This can be explained by the effects of watershed and roundness described above.…”
Section: Resultsmentioning
confidence: 78%
“…Due to the similar refractive index of water (1.3312 -1.3372) [4] and FEP (1.3380 -1.334) [5] a distortion-free observation of a water-based emulsion is carried out. Several further investigations confirm this experience [3,6,7]. A peristaltic pump (LabDos Easy-Load, HiTec Zang GmbH, Germany) pumps the emulsion through the analytic bypass, where it returns to the emulsion vessel.…”
Section: Methodsmentioning
confidence: 80%
“…Another reason might be the substance system itself because, for the crystallization investigations without the particle screw, the purity of the L-alanine was higher. Other investigations showed that purity influences this substance system regarding nucleation behavior, 43 which is probably the case for the growth kinetics. Another possibility could be that the particle screw causes a faster suspension discharge and that the crystals in the investigations made without the particle screw grew in the product tube because they settled and stayed there so that they could grow longer.…”
Section: Discussionmentioning
confidence: 92%
“…The same thermogravimetric method as described in ref and used already in refs and was used to determine the solid weight fraction ( w i ) of the suspension and to calculate the relative yield ( Y rel ) (eq ), which indicates how well the solubility line was reached and supersaturation was reduced. The relative yield needs the mass loading ( X i ) for determination.…”
Section: Methodsmentioning
confidence: 99%